GAMBARAN IDENTIFIKASI KADAR HAEMOGLOBIN DENGAN JENIS PENYAKIT MALARIA PADA ANAK DI RUANGAN PERAWATAN ANAK RSUD DR. H. CHASAN BOESOIRIE TERNATE TAHUN 2013: GAMBARAN IDENTIFIKASI KADAR HAEMOGLOBIN DENGAN JENIS PENYAKIT MALARIA PADA ANAK DI RUANGAN PERAWATAN ANAK RSUD DR. H. CHASAN BOESOIRIE TERNATE TAHUN 2013 - Rugaya M Pandawa; Rony Puasa (Jurnal Kesehatan, 2014)
Abstrak: This study was conducted to answer the question of how the image of the identification of hemoglobin with the type of malaria in children in the room Childcare dr. Chasan Boesorie Ternate. This type of research used in this study is an observational survey using a 'cross-sectional' where variables including risk factors and variables that include observational effects while at the same time to see hubunan Malaria In Children With Hemoglobin at room Childcare dr. Chasan boesorie ternate. Data collection techniques are the primary data is data that is collected directly from pediatric patients by means of interviews with observation using a questionnaire, then the secondary data is the data obtained from the child care room and laboratory results in dr. H.Chasan Boesorie Ternate. Furthermore, the management and analysis of the research data presented descriptively using tables and narrative. From the above research question that the number of samples in this study as many as 70 people were conscientious of men as much as 45 people (64.3%) and women as many as 25 people (35.7%). Based on these results there are differences in the percentage of patients by sex men and women, where male patients more than women, whereas the largest age group in the age group of 1-3 years as many as 22 people (31.4%) and the lowest in the age group of 4-6 years as many as 9 people (18.6%). The results of this study concluded that malaria vivax / tertian can affect the value of hemoglobin levels. Malaria can cause a decrease in hemoglobin concentration in the blood, which causes anemia. Furthermore, that type of malaria falsifarum have the effect of the reactor decreased levels of hemoglobin in children, and the last that ovale malaria can also reduce levels of hemoglobin in children, where the symptoms or manifestations of malaria are very diverse. The clinical picture is not purely one type of malaria, malaria is relatively mild and self-limiting. Furthermore, that for malaria quartana not found respondents with malaria during the study, so more research is needed